Triple mesh technique in repair of recurrent lumbar incisional hernia - Parikh, Archit Pankaj Kumar; Parikh, Parth; Vadodariya, Dhaval; Dave, Jignesh P.; Bhatt, Jatin G. (International Journal of Research in Medical Sciences, 2019)
Lumbar hernias occur infrequently and can be congenital, primary (inferior or Petit type, and superior or Grynfeltt type), post-traumatic, or incisional. They are bounded by the 12th rib, the iliac crest, the erector spinae, and the external oblique muscle. Most postoperative incisional hernias occur in nephrectomy or aortic aneurysm repair incisions for which various surgical method in context of meshplasty are available. In this case 60 yr. male hypertensive patient presented to the outpatient clinic of institute with recurrent left side lumbar incisional hernia, patient was previously operated for left side nephrolithiasis 15 years back and onlay meshplasty 2 years back for incisional hernia. The patient was operated under high risk for recurrent incisional hernia repair by triple layered meshplasties in the same sitting. Lumbar incisional hernias are often diffuse with fascial defects that are usually hard to appreciate. Computed tomography scan is the diagnostic modality of choice with adjuvant clinical findings, which allows differentiating them from abdominal wall musculature denervation atrophy complicating flank incisions. Repairing these hernias is difficult due to the surrounding structures for which our surgical approach included a triple mesh repair consisting of underlay, inlay and onlay meshplasty thereby anticipating further such incidences of incisional hernia.